Adsorption of Atenolol on Talc: An Indication of Drug Interference with an Excipient - Zhaohui Li; Nicole M. Fitzgerald; Guocheng Lv; Wei-Teh Jiang; Limei Wu (Adsorption Science & Technology)
Talc is commonly used as an excipient for drug formulations. The general expectation is that the excipient should have only minimal interactions with the carrying drug. In this study, the adsorption of atenolol (AT), a β-blocker, on talc, a clay mineral of pH-dependent surface charge, was evaluated under different physicochemical conditions such as the initial AT concentration, equilibrium time, solution pH, ionic strength and temperature. Our experiments showed that talc had an AT adsorption capacity of 11 mmol/kg. In addition, adsorption of AT on talc was instantaneous, which suggests that the adsorption sites were located on the external surfaces or edges. Factors such as solution pH, ionic strength and temperature all had minimal influence on AT adsorption, although the adsorption process was exothermic and the free energy of adsorption was negative, indicating weak physical adsorption. The Fourier transform infrared results showed blue shifts of the bands corresponding to δ(C–OH) at 1410 and 1043 cm −1 , indicating hydrogen bonding for the uptake of AT on talc surfaces or edges.